Tourism intensity impact on satisfaction with life of German residents. (December 2016) - Tokarchuk, Oksana; Gabriele, Roberto; Maurer, Oswin
Tourism researchers as well as policy makers are interested in knowing the impact of tourism on residents' life. Recent studies address this issue by looking at residents' quality of life measures. These studies, however, are based on convenience sample with investigation that is usually limited to one single destination at a given point of time. Socioeconomic characteristics of individuals have strong effect on the perception of tourism impact. In the present study, we investigate the impact of tourism intensity on residents' satisfaction with life using the theoretical framework of the bottom-up spillover theory. The analysis is based on a representative socioeconomic panel of German households over a period from 2000 to 2011. The analysis conducted involves the whole country distinguishing tourism destinations at administrative districts level. The empirical models suggest that tourism intensity and well-being of employed and unemployed residents present nonlinear U-shaped relationship. For low tourism intensities, residents' well-being is weakly affected while for higher intensities, the positive effect is stronger.